Prevalence and Risk Factors for Occupational Voice Disorders in Nepalese Teachers: A Cross-Sectional Study - Pokharel, Apar; Basnet, Puspa; Sharma, Bibek; Upadhyay, Hari Prasad (International Archives of Otorhinolaryngology, 2024)
Introduction Teachers are a high-risk group for the development of vocal dysfunction, as they use voice extensively in their profession.Objective To know the prevalence and risk factors associated with voice strain in teachers.Methods A cross-sectional study was conducted among schoolteachers in Chitwan, Nepal. The Voice Handicap Index questionnaire was used as a survey tool.Result A total of 315 teachers were enrolled in the study. The mean age of the participants was of 36.7 years. Teachers from public schools, primary grade classes, > 50 pupils in the classroom, > 24 hours of classes per week, dust in class, and recurrent tonsil problems were associated with various degrees of vocal handicap.Conclusion There is a high prevalence of voice disorder among teachers. A holistic approach, which includes teacher education regarding voice care during their work and management of their voice handicap by taking into consideration different risk factors, must be adopted.
Keywords: school teachers; voice disorder; voice fatigue